THE IMPACT OF REGIONAL INEQUALITY ON MIGRATION TRENDS IN LATVIA - Jeršova, Anastasija; Mietule, Iveta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The topic of current research and key findings are topical, taking into the consideration the territorial development tendencies of Latvia, which is characterized by the long-term regional inequalities and the tendencies of the migration of the population. The aim of the research is to analyse the impact of the regional inequalities on the migration tendencies of population in Latvia. The following research methods have been used in the research- logically constructive method, content analysis, monographic method, synthesis method, statistical analysis of interrelations, integral index method. Within the research, by using the selected research methods, authors have evaluated the influence of migration indicators-stimulators and indicators-de-stimulators on the migration trends in Latvia over time.